The effect of globalisation on industrial districts in Italy: evidence from the footwear sector - Roberta Rabellotti; Alessia Amighini (European Regional Science Association (ERSA), 2003)
One of the most pervasive and disruptive effects of globalisation is the fragmentation of production processes across countries. This phenomenon is the result of delocalisation strategies pursued by firms in industrialised countries to counter increasing competitive pressures from low labour-cost producers in emerging economies. Many Italian industrial districts are deeply interested by this phenomenon. This paper will be focussed on footwear industrial districts. In the Italian footwear sector the increasing globalisation of production is imposing major changes on the organisation of production: · on the one hand, evidence at a national level shows that increasing international competition is spurring a massive fragmentation of production processes through delocalisation of labour-intensive activities abroad (towards Eastern European countries, mainly Romania); · on the other hand, evidence from a previous study of one of the author on one of the most important footwear clusters - Riviera del Brenta - suggests that the overwhelming presence of fashion firms and increasing concentration in distribution is limiting producers' control on some crucial activities, i.e. design, branding, marketing, distribution (Rabellotti R., 2001, ?The effect of globalisation on industrial districts in Italy: the case of Brenta?, IDS Working Paper 144, Institute of Development Studies, Brighton). Overall, these trends are reducing the range of activities carried out within the districts. Consequently, as firms in industrial districts enter international production networks, they are altering their traditional sources of competitiveness, which has traditionally come from intra-cluster relationships. This paper is concerned with the effect of globalisation of production on footwear industrial districts in Italy. The aim is to investigate the changing role of footwear districts within international production networks. The following questions will be tackled: which is the pattern of specialisation of footwear districts in Italy? Is there any common trend towards a reduction of activities carried out within the districts' Or, instead, are different patterns emerging for districts according to their segment of market and according to the value chains they belong to? The paper will explore these issues by analysing the pattern of fragmentation of production in the footwear sector at a regional and ?provincia? level, using data on outward processing trade (OPT) collected by Associazione Nazionale Calzaturifici Italiani (ANCI). This will allow to understand delocalisation strategies by location and to answer the question of whether different trends are emerging at a regional level. By matching this information with the geographical distribution of footwear districts in Italy, it should be possible to throw some light on the pattern of specialisation of different districts. As regards the other trend which might impact on the pattern of specialisation of footwear districts - such as the emergence of big fashion firms in the luxury segment of the market? and which does not show up in the data, primary source information will be collected through surveys to producers in different footwear clusters, to complement the analysis above.
Keywords: 330